Financial accounting : for B Com (Hons), CA & CS (Foundation) courses - Maheshwari, S.N.; Maheshwari, S.K. (New Delhi : Vikas Publishing House PVT Ltd., 1993)
Section 1 of the book covers entire accounting cycle - from recording of financial transactions to the preparation of final accounts. Section 2 covers accounting problems relating to consignments, joint venture accounts etc.
Includes bibliographical references.
Loans
osc 21/6/16
Keywords: Financial Accounting